1978
DOI: 10.1111/j.1365-2222.1978.tb03221.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐specific IgE and IgG antibodies in pollen‐allergic children given immunotherapy for 2‐6 years

Abstract: Summary Ninety‐five children with pollen hay fever were treated for 46 months (16‐74 months) with extracts of birch pollen (seventy‐two children) and/or grass pollen (fifty‐nine children). During the first 2 months of this immunotherapy the serum concentration of allergen‐specific IgE antibodies doubled or tripled, but the concentration of IgG‘blocking’antibodies increased even more. With time the IgE antibody activity decreased in 80% of the children, but only in slightly more than 50% did it fall to below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…B. bei Patienten mit Rhinitis allergica, extrinsischem Asthma bronchiale oder insektengiftallergischen Reaktionen mittels Fluoreszenzimmunoassays in Serumproben nachgewiesen und gemäß WHO-Standard quantifiziert [8]. Zu Beginn der spezifischen Immuntherapie stellt sich in Analogie zur Situationen einer gesteigerten natür-lichen Allergenexposition zunächst eine vorübergehende Erhöhung des allergenspezifischen IgE (sIgE) ein, während sich im Verlauf der SIT in der Regel ein erneutes Absinken der sIgE-Spiegel beobachten lässt [9]. Zusätzlich konnte mithilfe placebokontrollierter Studien gezeigt werden, dass pollenallergische Patienten unter SIT einen signifikant niedrigeren saisonalen Anstieg des allergenspezifischen IgE aufwiesen als nicht behandelte Patienten [10,11].…”
Section: Allergenspezifische Ige-antikörperunclassified
“…B. bei Patienten mit Rhinitis allergica, extrinsischem Asthma bronchiale oder insektengiftallergischen Reaktionen mittels Fluoreszenzimmunoassays in Serumproben nachgewiesen und gemäß WHO-Standard quantifiziert [8]. Zu Beginn der spezifischen Immuntherapie stellt sich in Analogie zur Situationen einer gesteigerten natür-lichen Allergenexposition zunächst eine vorübergehende Erhöhung des allergenspezifischen IgE (sIgE) ein, während sich im Verlauf der SIT in der Regel ein erneutes Absinken der sIgE-Spiegel beobachten lässt [9]. Zusätzlich konnte mithilfe placebokontrollierter Studien gezeigt werden, dass pollenallergische Patienten unter SIT einen signifikant niedrigeren saisonalen Anstieg des allergenspezifischen IgE aufwiesen als nicht behandelte Patienten [10,11].…”
Section: Allergenspezifische Ige-antikörperunclassified
“…Well-controlled studies have convincing ly demonstrated the beneficial effects of IT for the treat ment of allergic rhinitis and asthma [2][3][4][5][6]; however, only a partial decrease in symptoms rather than 'cure' has been found. Immunological events that occur during IT include a rise in specific 'blocking' IgG antibodies, fall in specific IgE antibodies below pretreatm ent levels and finally, the induction of suppressor T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have described a suppression of the seasonal booster rise of the specific IgE anti bodies in pollen allergies [11,19,20,26] as a result of DT but others have not been able to confirm these findings [9,17,31]. Similarly, contradictory results have been reported regarding the reduction of the spe cific IgE antibody concentrations during the course of DT [5,8,17,18,22,28], Allergen-specific antibodies of the IgG type, some times called 'blocking antibodies', constantly appear during DT [25]. There seems to be a rough correlation between their appearance and rise and the clinical benefit of the treatment [9,25].…”
Section: Introductionmentioning
confidence: 61%